Deforestation, Carbon dioxide increase in the atmosphere and global warming: A modelling study. (4th May 2021) - Panja, Prabir
ABSTRACT: In this paper, a mathematical model has been formulated by considering carbon dioxide in the atmosphere, human population, forest biomass and global warming as separate compartments. It is assumed that human and forest biomasses grow logistically. It is assumed that the growth rate of human population is affected by global warming through different natural and human activities. Also, it is considered that global warming of the environment increases gradually due to the increase of carbon dioxide in the atmosphere as well as deforestation. Different equilibrium points have been determined. Also, the stability of our proposed system has been explored around these equilibrium points. Hopf bifurcation analysis have been done with respect to some important parameters of our proposed model. Finally, some numerical simulation results have been presented to verify our theoretical results.